Gambaran Tingkat Pengetahuan Pengobatan Tradisional Terhadap Masuk Angin Pada Masyarakat Desa Kota Agung - Anggun Dwi Rahma; Fenny Yunita (Jurnal Medika Nusantara, 2023)
Colds are considered a "common" disease in Indonesia, despite the fact that they can affect various aspects of life and can be fatal. The cure for colds generally uses traditional medicine where scrapings are usually chosen as the first cure, besides herbal medicine, especially those made from ginger extract so that air can get out of the body. This study aims to describe the level of knowledge about traditional medicine for scraping and the consumption of red ginger extract against colds in the people of Kota Agung Bengkulu Village in South Bengkulu in 2021. This study used a descriptive approach with a research sample of 86 people. Data collection techniques using closed questionnaires and data analysis techniques using descriptive analysis and simple statistics. The results showed that the characteristics of the people of Kota Agung Village, Seginim District, South Bengkulu Regency, Bengkulu Province who utilized traditional medicine for scrapings and consumed red ginger extract as a treatment for colds were dominated by female sex as much as 59%, 66% aged ? 45 years, 67% high school education. and have other jobs as much as 53%. The level of knowledge about kerokan traditional medicine and the consumption of red ginger extract against colds in the people of Kota Agung Village, Seginim District, South Bengkulu Regency, Bengkulu Province has a high level of knowledge, namely 87% for the level of knowledge of kerokan and consumption of red ginger extract, and 93% for the level of knowledge of kerokan and red ginger extract consumption. cold knowledge.